Informed Consent in the Workplace Nutrition Intervention Studies: A Narrative Review on Ethical Challenges - Narendraputra, Agra Dhira; Basrowi, Ray Wagiu (Ridwan Institute, 2024)
Workplace nutrition interventions are efforts to improve workers' health and well-being through education, counselling and environmental changes. Nutrition intervention studies are needed to evaluate the effectiveness of such programs and interventions. The aim of this study was to analyse studies on the importance and best practices of informed consent in workplace nutrition intervention studies and present the results in a narrative review. This study used qualitative research methods. The data collection technique in this research is by studying literature obtained from Google Scholar. The data collected was then analysed in three stages, namely data reduction, data presentation and drawing conclusions. The results showed that employees were fully aware of the nature of the intervention, its potential risks and benefits, and their right to withdraw from the study at any time7. This is important to respect employee autonomy and to ensure that research is conducted ethically. In conclusion, informed consent plays an important role in workplace nutrition intervention research. This not only protects the rights and welfare of employees but also contributes to the validity and ethical conduct of research.